Classroom implementation by Masbatenyo public elementary teachers of the mother tongue-based multilingual education policy: a case study - Barruga, Bernard M. (Language policy, 2025)
This study aimed to explore the implementation of the Mother Tongue-Based Multilingual Education (MTB-MLE) policy by public elementary teachers in the Philippines through a case study approach. Specifically, the study sought to examine how three elementary teachers in one public school institution distinctively implement the MTB-MLE policy in their classrooms. The study used a qualitative research design, specifically in-depth individual interviews with the selected teachers, to gather rich data about their experiences and practices in implementing the policy in order to shed light on the actual classroom practices of teachers in implementing the MTB-MLE policy, which has been mandated by the government to promote language and literacy development among young learners. The outputs of this study engage deeply with practices and experiences of selected teachers implementing the MTB-MLE policy. Key challenges include the scarcity of ready printed materials for MTB-MLE, perceptions of MTB-MLE as an additional subject burden, struggles with translating technical terms into local dialects, and the complexity of the policy itself. Opportunities identified include the potential for fostering deeper cultural connections among students, enhancing comprehension through native language instruction, and the pivotal role of parents in the MTB-MLE process. Considering these insights, this study advocates for the development of more localized learning materials, refining the policy to reduce perceived burdens, and initiatives to involve parents and address any negative attitudes. The implications of this research can influence policy and practice in education, improve instructional quality, and boost the language and literacy development of young learners in the Philippines. Further, this research contributes to refining Spolsky’s (Spolsky, Language policy, Cambridge University Press, 2004) theory of language policy, suggesting that it should incorporate the diverse linguistic resources available to actors, acknowledging status and hierarchies among languages. The study highlights the various considerations that may shape language preferences, proposing that a more illustrative language policy theory should prominently feature both the managers and those subject to the policy.